The metalogic futures model: a framework for transformational organizational and social change - M. Jayne Fleener; Victoria Vojnovich; Paula Berardinelli (European Journal of Futures Research)
Abstract This paper explores the question of engaging futures narratives to support and create transformational futures for organizations and social change efforts. Understanding organizational and social change and seeking fundamental change within organizations and social contexts requires deeper understandings of transformational learning and change at both individual and social dimensions. Building from adult learning scholarship on transformational learning, Inayatullah’s futures typology and Sardar’s three tomorrows as approaches to anticipatory futures are incorporated into a model that supports working within organizations and social change efforts. The metalogic futures model for social transformation incorporates futures literacy and transformative learning theory to serve as both a guide for engaging others in a transformative futures process and for evaluating transformative futures change initiatives with the purpose of escaping the bonds of what Bateson described as dormitive thinking. The metalogic futures model serves as an organizational tool for collaborative efforts to address organizational and social change and provides an analytical tool to understand the depth and levels of perspectives of change needed at individual and social dimensions for transformational change to occur. The intended audiences for this paper include futurists and futures researchers wishing to explore ideas about transformative learning as related to futures literacy, and adult educators wishing to explore futures literacy as related to adult learning theory, with both groups working in the context of organizational and social change.